Sow housing associated with reproductive performance in breeding herds. Issue 9 (8th June 2017) - Koketsu, Yuzo; Iida, Ryosuke
Abstract : Female pigs in breeding herds can be managed through four phases—gilt development, breeding, gestation, and lactation—during which they may be housed in group or individual pens, stalls, or on pasture. In this review, we focus on housing environments that optimize outcomes during gestation and lactation. Appropriate housing is important during early gestation, to protect embryos and to confirm pregnancy, and from mid‐to‐late gestation, to ensure sufficient nutrition to increase placental and fetal growth. No difference in the number of pigs born alive were reported between group housing and individual stall housing, although more risk factors for reproductive performance are associated with group housing than stall housing including genetics, bedding, floor space allowance, group size, social ranking, and parity. Furthermore, lameness in pregnant pigs is more frequent in group housing than in stall housing. Housing during lactation helps protect piglets from being crushed or from contracting disease, and can foster the transfer of enough colostrum from mother to piglets. Indeed, lactating sows in pen housing tend to have higher pre‐weaning mortality and lighter litter weights than those in crated housing.